Identification of Haemophilus parasuis using MALDI-TOF mass spectrometry - V. I. Pavelko; Yu. Yu. Babin; A. V. Piskunov; A. V. Sprygin; O. V. Pruntova (Ветеринария сегодня, 2018)
The paper covers results of MALDI-TOF mass spectrometry used to rapidly identify Haemophilus parasuis field isolates. ClinProTools software showed 15 peaks in the protein spectrum with 100% identification capability differentiating 6 Pasteurellaceae species. Peak corresponding to mass of 8407.92 Da (p